EFEKTIVITAS PENGGUNAAN APLIKASI SHOPEE PADA MASA PANDEMI COVID-19 DALAM PEMENUHAN KEBUTUHAN MASYARAKAT: (STUDI KASUS PADA MASYARAKAT KOTA TASIKMALAYA) - Fauzi, Ahmad; Suswandi, Alma Ghia Almanazh; Dewi, Ayu Sinta Sri (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2022)
This study aims to determine how effective the use of the Shopee application during the COVID-19 pandemic is in meeting community needs. Shopee is an application that gives its customers the opportunity to shop online with the many features it offers. During the COVID-19 pandemic, as it is today, many people prefer to shop online, one of which is the people in the City of Tasikmalaya, with many shopee users in the City of Tasikmalaya, this research was held. The research method used is descriptive quantitative. The results revealed that 99% of the people of Tasikmalaya City feel that the use of shopee during this pandemic has been effective because it can help the community meet their needs during the covid-19 pandemic.